Authority Analysis of Counting the State Financial Loss in the Investigation of Criminal Act of Corruption in Indonesia (Study at the BPK Representative Office and BPKP Lampung Province) - I Ketut Seregig; Bambang Hartono; R Riagung (Sociological Jurisprudence Journal, 2019)
The authority to calculate the state losses in corruption, until now, is still a problem that must be addressed with government policy in conducting investigations Audit Board of the Republic of Indonesia (BPK) and Financial and Development Supervisory Agency (BPKP). Both of these bodies in issuing products for calculating state losses, apply different process of completing the product of the investigation conducted. Information from Indonesian Republic Police (Polri) investigators prefer the BPKP as a partner in determining state losses in a criminal act upon request of the investigators to BPKP to calculate the state losses. The method used in this study normative research and the approaches used are juridical and empirical approaches. The results of the study is BPK pursuant to Law No. 15 of 2006 has the authority to calculate State losses carried out by the Main Investigator Auditor (AUI) which has the authority to conduct Investigation Examinations, Although the Supreme Audit Agency Acts and has the authority to calculate State losses,. In addition to the BPK there are other bodies that have the authority to calculate State lossesy, that is Corruption Criminal Investigators that are more likely to use BPKP to calculate State losses compared to BPK.